Corrosion properties of an aluminium alloy 7000 series after a new two step precipitation hardening - Biljana Bobić; Stanković Vesna Mišković (Zaštita Materijala)
Corrosion properties of an aluminium alloy 7000 series were investigated by different electrochemical methods. The alloy was subjected to the one-step and to a new two-step precipitation hardening. Polarization measurements in the 3.5 wt. % NaCl solution have shown a more positive value of the pitting potential (Epit) and a higher corrosion resistance for the two-step aged alloy. The electrochemical impedance spectroscopy (EIS) has also shown that the two-step aged alloy has better corrosion properties (higher value of polarization resistance, Rp, and lower value of double-layer capacitance, Cdl) comparing to the one-step aged alloy.